Pemanfaatan hounsfield unit pada CT-scan dalam menentukan kepadatan tulang rahang untuk pemasangan implan gigi - Barunawaty Yunus; Bachtiar Murtala (DiscoverSys Inc., 2010)
In the past, dental implant (DI)treatment is still an exclusive treatment can only beachieved by high class people due to unaffordable cost. However, nowadays thedemand of DI become increasing. The success of DI insertion is determined by thecondition of alveolar bone itself. Although there is no studies of DI treatment failurein Indonesia, there are some reports studied failure of DI treatment assessment whichcould be caused by the lack of quality and quantity of the alveolar bone radiographyimage. The purpose of this article was to introduce the benefit of hounsfield unit at theCT-Scan in supporting assessment of alveolar bone compactness for DI insertion. Itcan be concluded that the use of hounsfield unit at the CT-Scan can provide theclinician in determining the alveolar bone compactness prior to the DI treatment thatcan decrease the failure to occur.